Characteristics of colonic migrating motor complexes in neuronal NOS (nNOS) knockout mice - Spencer, Nick (Frontiers in Neuroscience, 2013)
It is well established that the intrinsic pacemaker mechanism that generates cyclical colonic migrating motor complexes (CMMCs) does not require endogenous nitric oxide (NO). However, pharmacological blockade of endogenous NO production potently increases the frequency of CMMCs, suggesting that endogenous NO acts normally to inhibit the CMMC pacemaker mechanism. In this study, we investigated whether mice with a life long genetic deletion of the neuronal nitric oxide synthase (nNOS) gene would show similar CMMC characteristics as wild type mice that have endogenous NO production acutely inhibited. Intracellular electrophysiological and mechanical recordings were made from circular muscle cells of isolated whole mouse colon in wild type and nNOS knockout (KO) mice at 350C. In wild type mice, the NOS inhibitor, L-NA (100µM) caused a significant increase in CMMC frequency and a significant depolarization of the CM layer. However, unexpectedly, the frequency of CMMCs in nNOS KO mice was not significantly different from control mice. Also, the resting membrane potential of CM cells in nNOS KO mice was not depolarized compared to controls; and the amplitude of the slow depolarization phase underlying MCs was of similar amplitude between KO and wild type offspring. These findings show that in nNOS KO mice, the major characteristics of CMMCs and their electrical correlates are, at least in adult mice, indistinguishable from wild type control offspring. One possibility why the major characteristics of CMMCs were no different between both types of mice is that nNOS KO mice may compensate for their life long deletion of the nNOS gene, and their permanent loss of neuronal NO production. In this regard, we suggest caution should be exercised when assuming that data obtained from adult nNOS KO mice can be directly extrapolated to wild type mice, that have been acutely exposed to an inhibitor of NOS.